Existe um efeito de borda na caatinga? : evidência de comunidades de liquens em Poço Verde, Sergipe - Dantas, Jaciele de Oliveira (2016)
The destruction and fragmentation of habitats for expansion of agricultural crops have contributed to the loss of diversity across the planet. One of the main consequences of fragmentation is the formation of artificial borders, which modify the microclimate and can trigger changes in biological processes. Such changes are termed edge effects and their magnitude depends on factors such as distance from the edge, size fragment, canopy structure, logging, vegetation matrix and taxonomic group. Lichenized fungi are sensitive to microclimate changes and are good predictors of human-induced disturbances. While edge effects in wet forest ecosystems are well studied, their impact on natural habitats of the Caatinga biome are still little explored. Thus, the aim of this study was to investigate whether the richness and species composition of corticicolous lichens changes over a edge-interior gradient resulting from forest fragmentation. The study was conducted in a remnant located in the Green Well municipality in the state of Sergipe, in Santa Maria da Lage. A total of 972 samples of corticicolous lichens were collected, distributed over 80 phorophytes corresponding to different distances from the edge (0 to 330 m). Among the samples, 182 species were identified, belonging to 16 families and 57 genera. There was no significant correlation between distance from the edge and species richness, but statistical analysis showed a significant difference in species composition related to edge distance. However, species richness was correlated with relative light intenity (canopy openness and diffuse transmittance). This work emphasizes the importance of the study of lichens in relation to the edge effect in the Caatinga, reinforcing the inclusion of these organisms in strategies for biodiversity conservation in this environment.